Assessment of WHO ten steps towards successful breastfeeding among postpartum mothers in Karaikal: A hospital based cross-sectional study - Farhan, Dr; Das, Sarthak; Malik, Archana (Asian Journal of Medical Sciences, 2018)
Background: Breastfeeding is the most essential, dynamic and profitable method of giving infants the perfect start in life. The Recent Rapid Survey on Children in India shows that 44.6% infants are now being breastfed within an hour of birth and 64.9 % of 0-6months old infants were exclusively breastfed. Aims and Objectives: To estimate the proportion of mothers who successfully breastfeed their children according to the WHO ten steps towards successful breastfeeding. Materials and Methods: A Cross-sectional study was conducted in Postpartum ward of JIPMER, Karaikal from 1st August to 31st September. Mothers aged 18- 49 years; given birth to healthy, singleton baby and stayed in hospital for minimum 24 hours after delivery were included in the study. The questions about breastfeeding practices based on “WHO ten steps of successful breastfeeding” were asked. Mothers knew seven steps or more(score ≥ 7) were considered as having successful breastfeeding. Results: Out of 205 only 32 (15.60%) mothers breastfeed their child successfully.There is significant difference between multiparous and primiparous mothers in Breastfeeding initiation within one hour of delivery(p=0.04) and Prelacteal feeding Practice (p = 0.003). The successful breastfeeding rate was higher among multiparous compared to primiparous mothers which is statistically significant (p=0.032). Conclusion: There is existence offaulty practice in breastfeeding process among post-partum mothers.The role of health professionals in encouraging optimal breastfeeding are remarkably low. Compulsory Implementation of BFHI in every hospitalby a Breastfeeding Committee, can be planned to increasing the breastfeeding rate. Asian Journal of Medical Sciences Vol.9(3) 2018 1-5